ESTIMATING MANUFACTURING COSTS FOR KOSOVOS’S SME THROUGH COMPARATIVE ANALYSIS - Lahu, Marigona (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
In this research, production costs were analyzed using data from accounting as a starting point. The objective was to demonstrate the calculation, estimation, and cost analysis based on the data from financial accounting in three distinct methods (accounting analysis, high-low and regression analysis) and to see the differences between those three methods. Each approach has benefits and drawbacks, and the best one to use will depend on the circumstances. The three techniques have produced a range of outcomes. We believe that the regression method is the most accurate of these three techniques. As we previously indicated, the majority of businesses in Kosovo, particularly small and medium-sized ones that struggle with personnel, lack the high knowledge and expertise in the division of Kosovo that is necessary for the technique of accounting analysis. Managers of small and medium-sized firms can benefit from this analysis by using it to identify the number of items that can be produced at the lowest cost and tailor it to the market's economic circumstances. In order to establish or alter their production volume and, indirectly, the sales price in terms of profitability, they must take into consideration the production costs, changes in the cost level of both the material component and the salary component, and other relevant factors. The high-low technique can be suitable if a rapid estimation is required. Although it is an examination of the past, it signifies the levels of activity that have been seen and the impacts that have been identified at each cost level The advantage of the Regression analysis is that this analysis can still be done without knowing the values of the fixed and total fixed costs. Creating the connection between fixed cost, variable cost, and quantity will aid managers in making decisions and enable cost planning and management. This investigation is constrained because we had trouble obtaining data from more manufacturing companies for a longer period of time.
Keywords: Costs, Regression analysis, Accounting analysis, High-low method